Behaviour of Gypsum Sheathed Point-symmetric Cold-formed Steel members: Assessment of AISI Design Method. (December 2019) - Selvaraj, Sivaganesh; Madhavan, Mahendrakumar
Abstract: This paper presents suggestions for the efficient codification of the current American Iron and Steel Institute's (AISI) design specifications for "Sheathing Braced Design of Wall Studs." The current design specifications of AISI is neither robust nor accurate, especially for various slendernesses, geometry (singly symmetric, double symmetric and point symmetric) and corresponding failure modes of the Cold-formed Steel (CFS) studs, since the current one was developed based on the limited experimental data. As per the author's knowledge, the current design expressions of AISI were not validated for various geometries of the CFS studs subjected to out-of-plane loading (perpendicular to the surface of the wall). Therefore, in this paper, 32 out-of-plane bending tests were carried out to understand the effect of gypsum sheathings in wall panels with "Z shaped" (point symmetric geometry) CFS structural members. The design parameters such as slendernesses of the CFS stud, sheathing board thickness and sheathing fastener connection spacing are considered. The experimental moment capacities and observed failure modes of the sheathed panels are compared with the AISI predictions. The comparison between experimental moment capacities versus AISI predictions indicates that the design predictions are unconservative due to the inability of the AISI design procedure in predicting the accurate failure modes of sheathed panels similar to experiments. Therefore, a set of modified design procedures in-terms of elastic buckling analysis model (EBAM) are suggested for predicting the accurate failure modes. However, even with the modified procedures, the design predictions are either overly conservative or unconservative, and this can be attributed to the fact that the study specimens are point symmetric whereas the components of sheathing stiffness values incorporated in the EBAM are based on the "singly symmetric" CFS studs alone. Nevertheless, the AISI implicitly suggests sheathing stiffness expressions (based on the C shaped CFS stud) for all types of CFS structural members. In addition, it was also observed that the current design procedures do not account for the variation in the slenderness of the CFS studs even for the "C shaped" CFS studs while predicting the sheathing stiffnesses which influences the strength of the members significantly. Hence, suggestions for improvement in the specific sections of the current AISI design provisions for effective design predictions are made.